Effectiveness Of Palliative Care Initiation in The Emergency Department in Reducing Healthcare Utilisation Among Adults with Life-limiting Illnesses: A Literature Review. - Yuan Xin WONG; Yen Tjuin Eugene TEOH (Singapore Nursing Journal)
Introduction This review examined current evidence regarding the effectiveness of palliative care (PC) initiation in the emergency department (ED) in reducing healthcare utilisation among adults with life-limiting illnesses (LLIs). Method A literature search was executed using PubMed, CINAHL, Cochrane Library, and ScienceDirect. Studies that assessed the efficacy of PC interventions implemented in the ED were included. These interventions were precisely characterised as referring patients to PC specialist services immediately, direct referral to PC or hospice care, consulting the PC service for ED patients, or administering PC interventions while the patient was still in the ED. The outcome of interest focuses on the effectiveness of ED-based PCs in reducing healthcare utilisation. Results Three themes were identified: (i) hospital and ED length of stay (LOS), (ii) Intensive Care Unit (ICU) admission rates, and (iii) healthcare costs and utilisation of healthcare resources. The findings suggest that initiating PC in the ED holds promise as a strategy to optimise healthcare utilisation and enhance the care experience for this vulnerable patient population. Conclusion The PC initiation in the ED significantly reduces healthcare utilisation metrics. However, its impact on reducing avoidable acute admissions remains uncertain.